Design and Analysis of Solar-powered E-bike Charging Stations to Support the Development of Green Campus - Slamet Suripto; Gilang Ari Widodo Utomo; Kunnu Purwanto; Karisma Trinanda Putra; Muhammad Yusvin Mustar; Mosiur Rahaman (Universitas Muhammadiyah Yogyakarta, 2022)
Currently, conventional motorcycles that utilize hazardous fossil fuels are expanding rapidly in Indonesia's major cities. Especially in campus environments, the increase in motorcycle usage has the potential to raise emissions of greenhouse gases and toxic microparticles. The green campus concept entails that campus living must implement low-emission energy efficiency, conserve resources, and enhance environmental quality by teaching its residents how to live a healthy lifestyle. However, limiting the number of motorcycles on campus is the main challenge, especially in Indonesia. To overcome this challenge, this study provides a design for the e-bike system that will be implemented at Universitas Muhammadiyah Yogyakarta (UMY). In addition, a solar power plant is integrated into the design to support the adoption of the zero-emission green energy concept on the campus. The design accommodates specifications for a 6 km radius surrounding the school, a two-day lifespan, and 100 electric bicycles. The experiment's findings indicate that the solar-powered e-bike design requires 99 solar panels with a capacity of 150 Wp, 9 SSCs with a capacity of 100 A, and three inverters with a capacity of 2,500 W. It is projected that this device will reduce exhaust emissions by 7.62 tons of CO2 per year once it is entirely operated.